Biogas and biomethane production routes in the sugar-energy sector: economic efficiency and carbon footprint - Fava, Flávio Eduardo (2023)
Efforts to fulfill the goals of mitigating climate change by replacing fossil fuels with renewable sources are increasing worldwide. In Brazil, the sugar-energy sector is one of the main responsible for decarbonizing the energy matrix, through ethanol and cogenerated electricity. However, new products have emerged using by-products of ethanol distillation, such as vinasse, which can be a source for biogas and biomethane. This study compared two routes for using biogas vinasse: bioelectricity cogeneration and biomethane production through economic and greenhouse gas (GHG) mitigation analyses and develop a model able to estimate the financial gains from their use, commercialization, considering the carbon footprint variation. The considered routes were identified to increase the earnings before interest, taxes, depreciation, and amortization (EBITDA) of producers based on projected prices and operational expenses (OPEX). They combined complementarily bioelectricitybiomethane mixes, taking into consideration the carbon mitigation from each route. The scenario with maximum biomethane production can generate an 38% higher EBITDA than the maximum generation of bioelectricity, in the first year. Yet, the estimated performance up to 2031 would be better in the scenario of maximum biomethane production, 54% growth compared to 46% for bioelectricity.